Sub-Regional Cooperation of the Republic of Moldova on the South-East European Dimension - Maria DIACON (Eastern European Journal of Regional Studies, 2017)
Formation of the country image on the world arena can be analyzed from the perspective of sub-regional cooperation. In this respect, we emphasize that Moldova has joined a number of initiatives, programs and organizations which, by their status and the range of the promoted objectives, became "antechamber" to the European Union. Fixing the borders of the sub-regional cooperation area, we note that in the Central Europe Moldova attends the Central European Initiative, while in the South-East Europe are carried out activities in the South-East European Cooperation Process and the Organization for the Black Sea Economic Cooperation and assists in the Organization for Democracy and Economic Development GUAM.